2014
DOI: 10.1007/s11064-014-1385-0
|View full text |Cite
|
Sign up to set email alerts
|

Tibolone Prevents Oxidation and Ameliorates Cholinergic Deficit Induced by Ozone Exposure in the Male Rat Hippocampus

Abstract: Oxidative stress is related to the development of central nervous system diseases involving memory processes. Cholinergic system and memory processes are disrupted by ozone exposure. In rats, ozone induces motor disturbances and memory deficits as well as biochemical changes in brain regions related to memory processes. In this work, we analyzed the effect of chronic tibolone (TIB) administration in central nervous system, specifically the content of choline acetyltransferase, acetylcholinesterase, acetylcholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 55 publications
1
22
0
4
Order By: Relevance
“…On the other hand, there was no additive effect for each arylimide in combination with propranolol. This result could be related to the shared region for the binding of these compounds on AChE, which is in agreement with the idea that the inhibition of this enzyme is the main mechanism of action for modulating the memory performance in the presently employed animal model (Farfán‐García et al, ; Mitsushima et al, ). However, other mechanisms have been mentioned for the modulation of the activity or expression of adrenoceptors in the brain (Ciprés‐Flores et al, ; Dobarro et al, ; Liu, Ma, et al, ; Lonergan et al, ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…On the other hand, there was no additive effect for each arylimide in combination with propranolol. This result could be related to the shared region for the binding of these compounds on AChE, which is in agreement with the idea that the inhibition of this enzyme is the main mechanism of action for modulating the memory performance in the presently employed animal model (Farfán‐García et al, ; Mitsushima et al, ). However, other mechanisms have been mentioned for the modulation of the activity or expression of adrenoceptors in the brain (Ciprés‐Flores et al, ; Dobarro et al, ; Liu, Ma, et al, ; Lonergan et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Eighty male rats were randomly divided into eight experimental groups ( n = 10). In Group 1, the control animals were sham‐operated (Farfán‐García et al, ; Wang & Xiang, ) and treated with the vehicle for 15 days. The animals in Groups 2–8 were orchiectomized and treated by oral administration for 15 days with vehicle (Group 2), neostigmine (14 μg/kg, Group 3), propranolol (571 μg/kg, Group 4), compound C7 (70 μg/kg, Group 5), compound C8 (70 μg/kg, Group 6), compound C7 and propranolol (Group 7), or compound C8 and propranolol (Group 8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tibolone (1 mg/kg; Livial®, Organon, Mexico) or vehicle (water) was administered daily by oral gavage for seven days. It has been recently demonstrated that this dose of TB has neuroprotective properties by reducing lipid peroxidation and ameliorating behavioral/functional deficits after ozone exposure [12,17]. The solutions containing TB or vehicle were independently coded before administration (▶ Fig.…”
Section: Treatmentsmentioning
confidence: 99%
“…Tibolone (TB), a synthetic steroid that has been used as an elective treatment for the relief of menopausal symptoms, and its various metabolites have estrogenic as well as progestogen/androgenic effects [11]. TB treatment in rats decreased OS markers [12], body weight, and total cholesterol levels [13], whereas in studies conducted with postmenopausal women, TB improved blood pressure, glycemia [14], insulin levels, HDL cholesterol, and triglycerides [15]. However, the acute effects of HT with TB on metabolic parameters and OS markers associated with the first stages of ED are still unknown.…”
Section: Introductionmentioning
confidence: 99%